2020
DOI: 10.1111/ppc.12592
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction, life quality, and leisure satisfaction in health professionals

Abstract: This study was aimed to determine the relationships between life satisfaction, life quality, and leisure satisfaction in health professionals. Design and Methods:The study was conducted with 498 health professionals working in a city of the Central Anatolia Region, Turkey. Data were collected using Socio-Demographic Form, the Satisfaction with Life Scale, the Short Form of World Health Organization Quality of Life Questionnaire, and the Leisure Satisfaction Scale.Findings: There was a positive significant rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 43 publications
1
19
1
1
Order By: Relevance
“…Among them, the content of leisure activities, enhancing self-confidence and physical fitness, restoring physical and mental health and physical strength, increasing knowledge and social interaction, self-exploration, and relaxation, experience, and feelings toward the environment can be obtained in more in-depth discussions. Additionally, research has pointed out that different background cognitions will produce differences [65,66].…”
Section: Leisure Satisfaction and Revisit Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the content of leisure activities, enhancing self-confidence and physical fitness, restoring physical and mental health and physical strength, increasing knowledge and social interaction, self-exploration, and relaxation, experience, and feelings toward the environment can be obtained in more in-depth discussions. Additionally, research has pointed out that different background cognitions will produce differences [65,66].…”
Section: Leisure Satisfaction and Revisit Intentionmentioning
confidence: 99%
“…Therefore, mixed research methods were used, quantitativ research methods were first used to supplement the research breadth [67,68], then qual tative research was used to increase the depth of research [69], and multivariate verifica tion methods were used to discuss [70][71][72], which could make up for research develop ment or defects of insufficient theory [73]. Therefore, the research first referred to the com piled questionnaire tools in the literature on leisure satisfaction [25,44,45,[57][58][59][60][61][62][63][64][65][66], physica and mental health, [25,44,45,[58][59][60][61][62], and willingness to participate again [25,44,45,[50][51][52][53][54][55] First, three experts checked the content validity. After the draft was revised, 100 question naires were collected in June 2020, analyzed using SPSS 26.0 statistical software, and con firmed with the formal questionnaire tools.…”
Section: Research Process and Frameworkmentioning
confidence: 99%
“…The activity theory also suggests that the more active the participation in free-time activities, the greater the happiness and life satisfaction [ 48 , 49 ]. Since numerous studies have reported a positive relationship between leisure satisfaction and life satisfaction [ 50 , 51 , 52 , 53 , 54 ], measuring whether working mothers are satisfied with their leisure experiences may provide important data for developing strategies or programs to help working mothers lead more fulfilled lives [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, they are suffering from boarding house and transportation problems, which constantly threaten the physical security from sexual abuse of women workers. Thus, most of their life satisfaction depends on these seven domains, as indicated by many researchers in their studies, such as workplace support on life satisfaction [38,39]; health satisfaction and life satisfaction [40,41];finance and life satisfaction, [42]; family and life satisfaction, [43,44,45]; leisure satisfaction and life satisfaction [46,47]; community and housing satisfaction [48,49]; housing satisfaction [50].…”
Section: Discussionmentioning
confidence: 99%